2020
DOI: 10.1088/1755-1315/456/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production from Kesambi (Schleichera oleosa) oil using multi-walled carbon nanotubes supported zinc oxide as a solid acid catalyst

Abstract: The development of heterogeneous catalysts for biodiesel production became a hot topic among scientists because of its many advantages including easy separation and catalyst reusability. In this study, multi-walled carbon nanotubes supported zinc oxide (MWCNTsZ) as a solid acid catalyst had been successfully prepared via the stober-like process. There are several % loading of ZnO variations ranging from 10 – 35 % of catalyst weight. These catalysts were characterized by x-ray diffraction (XRD), BET surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Rad et al utilized sulfonated carbon nanotubes (S-MWCNTs) in the transesterification and esterification of sunflower oils and chicken fat to convert them to biodiesel with a yield of 96.1% in the case of sunflower oil and 93.7% using waste chicken fat oil in the presence of methanol at a ratio of 6:1 and 1 wt % catalyst concentration for 1 h at 60 °C . Carbon catalysts for biodiesel production have been reported for the deoxygenation reaction in the presence of single metal oxide as well as in the presence of MWCNTs enhanced with bimetal oxide . Asri et al prepared and evaluated zinc-oxide-enhanced carbon nanotubes (ZnO/MWCNTs) for biodiesel preparation using kesambi oil (Schleichera oleosa L.).…”
Section: Carbon-based Catalystsmentioning
confidence: 99%
“…Rad et al utilized sulfonated carbon nanotubes (S-MWCNTs) in the transesterification and esterification of sunflower oils and chicken fat to convert them to biodiesel with a yield of 96.1% in the case of sunflower oil and 93.7% using waste chicken fat oil in the presence of methanol at a ratio of 6:1 and 1 wt % catalyst concentration for 1 h at 60 °C . Carbon catalysts for biodiesel production have been reported for the deoxygenation reaction in the presence of single metal oxide as well as in the presence of MWCNTs enhanced with bimetal oxide . Asri et al prepared and evaluated zinc-oxide-enhanced carbon nanotubes (ZnO/MWCNTs) for biodiesel preparation using kesambi oil (Schleichera oleosa L.).…”
Section: Carbon-based Catalystsmentioning
confidence: 99%
“…For the esterification of fatty acid derived from palm, Shuit et al reported employing sulfonated multiwalled carbon nanotubes (s-MWCNT) [ 112 ]. Loading of ZnO nanoparticles on microwalled carbon nanotubes (MWCNT) led to decrement of surface area and increment of active sites, enhancing rate of reaction and mass transfer [ 113 ].…”
Section: Nanomaterials In Transesterificationmentioning
confidence: 99%
“…Biodiesel conversion of 85% was obtained with the simultaneous use of the nanocatalyst for 95 h without losing its structural integrity and morphology (Zhang et al, 2014). Another group (Asri et al, 2020) reported the synthesis of multiwalled CNT loaded with varying ZnO nanoparticles. The developed heterogeneous solid acid nanocatalysts have been utilized for trans-esterification of Kesambi oil giving methyl esters production of 13.82% while using only 20 wt% of ZnO loaded MWCNT.…”
Section: Carbon Based Nanocatalystsmentioning
confidence: 99%
“…Carbon nanotubes mainly possess high specific surface area, but its surface area has been reduced greatly upon ZnO loading. The active sites predominantly increase, ultimately increasing the reaction rate and overall activity of the nanocatalyst, also the mass transfer is greatly reduced (Asri et al, 2020). also reported the use of sulphonated multiwalled carbon nanotubes (s-MWCNT) for esterification of palm fatty acid distillate.…”
Section: Carbon Based Nanocatalystsmentioning
confidence: 99%